Foreign Currency Bank Funding and Global Factors - Krogstrup, Signe (IMF Working Papers; Working Paper, 2018)
The literature on the drivers of capital flows stresses the prominent role of global financial factors. Recent empirical work, however, highlights how this role varies across countries and time, and this heterogeneity is not well understood. We revisit this question by focusing on financial intermediaries' funding flows in different currencies. A concise portfolio model shows that the sign and magnitude of the response of foreign currency funding flows to global risk factors depend on the financial intermediary's pre-existing currency exposure. An analysis of a rich dataset of European banks' aggregate balance sheets lends support to the model predictions, especially in countries outside the euro area.